THE ROLE OF FUNCTIONAL BREADS IN THE DAILY DIET (International Conference on Modern Science and Scientific Studies, 2024)
Functional breads have gained considerable attention in recent years due to their potential health benefits beyond basic nutrition. This article explores the significance of incorporating functional breads into the daily diet, highlighting their diverse range of ingredients and the impact on overall health and well-being. Through a comprehensive literature analysis, this article examines the potential methods of enhancing bread functionality, the current research landscape, and the implications for dietary recommendations. The findings suggest that functional breads can play a valuable role in promoting a balanced and nutritious diet, offering consumers an accessible way to improve their health.